2020
DOI: 10.3390/ijerph17186509
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Loss Thresholds Reliably Control Kinetic and Kinematic Outputs during Free Weight Resistance Training

Abstract: Exercise velocity and relative velocity loss thresholds (VLTs) are commonly used in velocity-based resistance training. This study aims to quantify the between-day reliability of 10%, 20%, and 30% VLTs on kinetic and kinematic outputs, changes in external load, and repetition characteristics in well-trained athletes. Using a repeated, counter-balanced crossover design, twelve semi-professional athletes completed five sets of the back squat with an external load corresponding to a mean concentric velocity of ~0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…However, this argument does not discount that the number of repetitions performed before reaching different VL thresholds might also have a high inter-individual variability. Indeed, this contention seems to be empirically supported because data from two recent studies [ 21 , 81 ] suggest that the number of repetitions performed until reaching 10, 20, and 30% VL in the free-weight back squat exercise is not only highly variable between individuals but is also unstable across sessions. In addition, this inter-individual variability may increase as the magnitude of VL increases [ 21 ].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, this argument does not discount that the number of repetitions performed before reaching different VL thresholds might also have a high inter-individual variability. Indeed, this contention seems to be empirically supported because data from two recent studies [ 21 , 81 ] suggest that the number of repetitions performed until reaching 10, 20, and 30% VL in the free-weight back squat exercise is not only highly variable between individuals but is also unstable across sessions. In addition, this inter-individual variability may increase as the magnitude of VL increases [ 21 ].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, both factors tend to have a strong inverse relationship with load, as higher loads allowed for fewer repetitions and produced lower variability in repetitions across VL thresholds. This is a previously overlooked outcome as studies often focus on the ability of VL thresholds to modulate, with acceptable reliability, the percentages of the completed repetitions per set with respect to the maximum number of repetitions possible [ 15 , 17 ] and kinetic and kinematic outputs [ 21 , 62 , 81 ]. Although these aspects of VL thresholds present an advantage over traditional methods for prescribing RT volume, the effects of the variability of the actual number of repetitions performed before reaching a certain VL threshold have not yet been empirically investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A possible solution for basketball researchers and practitioners to gather strength data from their players is to use a linear position transducer (LPT) during resistance training sessions to measure kinetic and kinematic outputs [36,171]. The use of an LPT during strength training can provide valid and reliable performance data [172], which is able to be tracked over time to monitor player progression (e.g., changes in bar speed at a specified load) [171,173], and used to predict maximal strength whilst inducing minimal fatigue [171,174,175]. Only one study [121] reported bench press 1RM relative to playing position in adult male basketball players.…”
Section: Strengthmentioning
confidence: 99%
“…This accuracy during the back squat and bench press is important; it is advised that mean velocity is used to monitor performance because this variable has improved reliability when developing load-velocity profiles and has lower between-athlete variability in the velocity attained at 1RM (8,21). This suggests that the Perch can be used across a range of diverse monitoring and prescriptive methods including velocity loss thresholds (10,16,22) and 1RM estimation (5,7,9).…”
Section: Discussionmentioning
confidence: 99%